The genus Scutibracon Quicke & Walker (Hymenoptera: Braconidae) in Vietnam, with new records and descriptions of two new species - Samartsev, Konstantin G.; Duong, Tran Dinh; Long, Khuat Dang (Zootaxa, 2025)
The genus Scutibracon and four its species are newly recorded in the fauna of Vietnam. Two new species, Scutibracon rugosus Samartsev, Duong & Long, sp. nov., and S. storozhenkoi Samartsev, Duong & Long, sp. nov., are described and diagnoses of S. hispae and S. sumodani are specified. An updated key to four species known from Vietnam is provided along with illustrations of all recorded species.